Flow Devices to Assess Platelet Function: Historical Evolution and Current Choices - Silva, Raisa Cintra Lomanto Santos; Grabowski, Eric Franklin (Seminars in Thrombosis and Hemostasis, 2019)
Platelet function testing, which began more than a hundred years ago, is a time-consuming and uncertain process. Simulating hemostasis and the blood vessel microenvironment in vitro is challenging, which poses a difficulty for diagnosing platelet dysfunction and mild von Willebrand disease (VWD). In an effort to simulate the rheological microenvironment within blood vessels, several blood flow devices have been introduced since the 1980s. These devices are capable of reproducing the shear rates found in arterioles and venules, and of incorporating endothelial cell monolayers and surfaces with adsorbed platelet-adhesive proteins. The authors will describe and review here the presently most well-known blood flow devices. The technologies inherent in these devices offer a combination of physiologic accuracy and small blood volume requirements in the evaluation of platelet disorders and mild VWD (or “symptomatic low von Willebrand factor”) in flowing whole blood, with the potential to individualize therapeutic options for and to achieve greater diagnostic accuracy in mild platelet disorders and VWD.
Keywords: microfluidics; platelet aggregation; platelet function testing; von Willebrand factor; von Willebrand disease